The breach of professional code of ethics under the Legal Profession Act 1976 with specific reference to Criminal Breach of Trust (CBT) / Jayniesa Lavang Jarit … [et al.] - Jarit, Jayniesa Lavang; Zainal, Farah Amirah; Mohd Fahmi, Mustabshira; Nadjmi, Mohammad Asghar (2014)
This research is conducted in order to study the breach of professional code of ethics in relation to criminal breach of trust (CBT) by legal practitioners. The research looks into the Legal Profession Act 1976 specifically Section 94 which is about professional misconduct. Other than that, this research will also look into the Solicitor Account Rules 1990 (SAR) which governs the lawyers in handling and managing the client's money. Apart from that, this research will also include the reason why lawyers committed CBT although being governed by LPA 1976 and SAR 1990 and also determine comprehensiveness of the Act to govern legal practitioners from committing CBT. In addition, comparison was made between the legal practice in United Kingdom and Singapore in handling CBT committed by legal practitioners. Thus, recommendations were made to deter the legal practitioners from committing CBT.